Galectin-9 Regulates Monosodium Urate Crystal-Induced Gouty Inflammation Through the Modulation of Treg/Th17 Ratio - Mansour, Adel Abo; Raucci, Federica; Saviano, Anella; Tull, Samantha; Maione, Francesco; Iqbal, Asif Jilani (Frontiers in Immunology, 2021)
Gout is caused by depositing monosodium urate (MSU) crystals within the articular area. The infiltration of neutrophils and monocytes drives the initial inflammatory response followed by lymphocytes. Interestingly, emerging evidence supports the view that in situ imbalance of T helper 17 cells (Th17)/regulatory T cells (Treg) impacts the subsequent damage to target tissues. Galectin-9 (Gal-9) is a modulator of innate and adaptive immunity with both pro- and anti-inflammatory functions, dependent upon its expression and cellular location. However, the specific cellular and molecular mechanisms by which Gal-9 modulates the inflammatory response in the onset and progression of gouty arthritis has yet to be elucidated. In this study, we sought to comprehensively characterise the functional role of exogenous Gal-9 in an in vivo model of MSU crystal-induced gouty inflammation by monitoring in situ neutrophils, monocytes and Th17/Treg recruited phenotypes and related cyto-chemokines profile. Treatment with Gal-9 revealed a dose-dependent reduction in joint inflammation scores, knee joint oedema and expression of different pro-inflammatory cyto-chemokines. Furthermore, flow cytometry analysis highlighted a significant modulation of infiltrating inflammatory monocytes (CD11b+/CD115+/LY6-Chi) and Th17 (CD4+/IL-17+)/Treg (CD4+/CD25+/FOXP-3+) cells following Gal-9 treatment. Collectively the results presented in this study indicate that the administration of Gal-9 could provide a new therapeutic strategy for preventing tissue damage in gouty arthritic inflammation and, possibly, in other inflammatory-based diseases.